Digital Technologies in the Financial sector: Evolution and Major Development Trends in Russia and Abroad - D. A. Artemenko; S. V. Zenchenko (Финансы: теория и практика)
The subject of the research is a complex of financial technologies that are actively used in the financial and credit sector in Russia and abroad. The study aims to show the place of technological progress based on the use of FinTech and the development of human capital in the Russian economy; transformation of business processes based on modern financial technologies, creating new promising opportunities, and responding to the challenges of Industry 4.0. The paper considers the issues related to the study of the prospects for the development of financial technologies in global practice and the possibilities of their adaptation in the activities of Russian financial organizations. The research is based on the analysis of data provided by international consulting companies, analytical centers, and official data sources of the Central Bank (Bank of Russia). The authors apply methods such as comparative research, empirical, logical, graphical, analysis, interpretation, and comparison. The study assesses the growing role of financial technologies in the Russian economy, identifies the main problems, and outlines development prospects based on the integration of traditional institutions and FinTech companies for the reproduction of financial innovations in the future. As a result, it was concluded that improving the technological effectiveness of banking processes is possible on the basis of digitalization using various financial technologies, which will lead to the simplification and optimization of traditional operations, prevention of fraud, create new and more personalized offers according to customer needs, while changing the way of interaction with them.